Use of motorised transport and pathways to childbirth care in health facilities: Evidence from the 2018 Nigeria Demographic and Health Survey - Cephas Ke-on Avoka; Aduragbemi Banke-Thomas; Lenka Beňová; Emma Radovich; Oona M. R. Campbell (Public Library of Science (PLoS), 2022)
In Nigeria, 59% of pregnant women deliver at home, despite evidence about the benefits of childbirth in health facilities. While different modes of transport can be used to access childbirth care, motorised transport guarantees quicker transfer compared to non-motorised forms. Our study uses the 2018 Nigeria Demographic and Health Survey (NDHS) to describe the pathways to childbirth care and the determinants of using motorised transport to reach this care. The most recent live birth of women 15-49 years within the five years preceding the NDHS were included. The main outcome of the study was the use of motorised transport to childbirth. Explanatory variables were women's socio-demographic characteristics and pregnancy-related factors. Descriptive, crude, and adjusted logistic regression analyses were conducted to assess the determinants of use of motorised transport. Overall, 31% of all women in Nigeria used motorised transport to get to their place of childbirth. Among women who delivered in health facilities, 77% used motorised transport; among women referred during childbirth from one facility to another, this was 98%. Among all women, adjusted odds of using motorised transport increased with increasing wealth quintile and educational level. Among women who gave birth in a health facility, there was no difference in the adjusted odds of motorised transport across wealth quintiles or educational status, but higher for women who were referred between health facilities (aOR = 8.87, 95% CI 1.90-41.40). Women who experienced at least one complication of labour/childbirth had higher odds of motorised transport use (aOR = 3.01, 95% CI 2.55-3.55, all women sample). Our study shows that women with higher education and wealth and women travelling to health facilities because of pregnancy complications were more likely to use motorised transport. Obstetric transport interventions targeting particularly vulnerable, less educated, and less privileged pregnant women should bridge the equity gap in accessing childbirth services.